Economic corruption and its social consequences It is a sociological study - Abdullah, M. Sangar Hossam Abdullah; Ahmed, L.Omar Ali Ahmed (Sulaimani Journal for Humanities, 2025)
Economic corruption is relatively common in all societies, but its causes, motives, and types differ from one society to another, so its effects and consequences take different directions. This study aims to identify the types, methods, causes and motives of economic corruption in the world in general and in the Kurdistan Region - Iraq in particular. The study also aims to identify the social effects of economic corruption on Kurdish society and provide suggested strategies to reduce the phenomenon of economic corruption.